SEMIOTIC ANALYSIS OF HUMAN BEHAVIOR IN FUFUFAFA ACCOUNT X - Wijaya; Nanda Dwi Rizka; Damayanti Masduki; Yuliani Widianingsih; Umi Rahmawati (JURNAL ILMIAH EDUNOMIKA, 2025)
ABSTRACT This research is a literature study so that no special location is needed for research because the object being studied is a literary manuscript (text), namely tweets in the x Fufufafa account. The data obtained from this study are secondary data that researchers obtained from direct tweets from the fuffafa account. The data were analyzed by stages of data collection, data selection, data reduction, and drawing conclusions with a comprehensive explanation. The result in this article show the owner of the Fufufafa account, whoever it is, has bad human behavior because the sentences made in the account allude to non-substantive personal problems. The account owner cannot be categorized as a critical person because the object of criticism is not public policy and common problems but personal problems. Therefore, the researcher concludes that the human behavior of the Fufufafa account has a bad direction. Keywords: Fufufafaf, Human Behavior, Account X